Model Pembelajaran Biologi Berbasis Lingkungan melalui Pendekatan Inquiry-Based Learning di MI NW Miftahul Ulum - Nikmah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2026)
This study examines the effectiveness of an environmental-based biology learning model using the Inquiry-Based Learning (IBL) approach in improving students’ learning outcomes, scientific literacy, critical thinking, and environmental awareness. A quasi-experimental design with a non-equivalent control group was applied to fifth-grade students at MI NW Miftahul Ulum. Data were collected through tests, observations, and questionnaires, and analyzed using t-tests and N-Gain. The findings reveal that the experimental group outperformed the control group, with moderate to high improvement levels. The IBL approach also enhanced students’ scientific literacy, critical thinking, and environmental awareness. Thus, environmental-based IBL is effective in creating meaningful and contextual biology learning at the primary level..